Unlocking microalgal host—exploring dark-growing microalgae transformation for sustainable high-value phytochemical production - Jareonsin, Surumpa; Mahanil, Kanjana; Phinyo, Kittiya; Srinuanpan, Sirasit; Pekkoh, Jeeraporn; Kameya, Masafumi; Arai, Hiroyuki; Ishii, Masaharu; Chundet, Ruttaporn; Sattayawat, Pachara; Pumas, Chayakorn (Frontiers in Bioengineering and Biotechnology, 2023)
Microalgae have emerged as a promising, next-generation sustainable resource with versatile applications, particularly as expression platforms and green cell factories. They possess the ability to overcome the limitations of terrestrial plants, such non-arable land, water scarcity, time-intensive growth, and seasonal changes. However, the heterologous expression of interested genes in microalgae under heterotrophic cultivation (dark mode) remains a niche area within the field of engineering technologies. In this study, the green microalga, Chlorella sorokiniana AARL G015 was chosen as a potential candidate due to its remarkable capacity for rapid growth in complete darkness, its ability to utilize diverse carbon sources, and its potential for wastewater treatment in a circular bioeconomy model. The aims of this study were to advance microalgal genetic engineering via dark cultivation, thereby positioning the strain as promising dark-host for expressing heterologous genes to produce high-value phytochemicals and ingredients for food and feed. To facilitate comprehensive screening based on resistance, eleven common antibiotics were tested under heterotrophic condition. As the most effective selectable markers for this strain, G418, hygromycin, and streptomycin exhibited growth inhibition rates of 98%, 93%, and 92%, respectively, ensuring robust long-term transgenic growth. Successful transformation was achieved through microalgal cell cocultivation with Agrobacterium under complete darkness verified through the expression of green fluorescence protein and β-glucuronidase. In summary, this study pioneers an alternative dark-host microalgal platform, using, Chlorella, under dark mode, presenting an easy protocol for heterologous gene transformation for microalgal host, devoid of the need for expensive equipment and light for industrial production. Furthermore, the developed genetic transformation methodology presents a sustainable way for production of high-value nutrients, dietary supplements, nutraceuticals, proteins and pharmaceuticals using heterotrophic microalgae as an innovative host system.